Highly Flexible, Conductive, and Antibacterial Surfaces Toward Multifunctional Flexible Electronics - Ruzgar, Duygu Gazioglu; Akin, Semih; Lee, Seungjun; Walsh, Julia; Lee, Hyowon Hugh; Jeong, Young Hun; Jeon, Yongho; Baek, Seung Yub; Jun, Martin Byung Guk (International Journal of Precision Engineering and Manufacturing - Green Technology, 2024)
Conductive metallization of polymer surfaces, owing to the integration of unique features of dissimilar materials (i.e., polymer + metal), is becoming the central focus in flexible polymer electronics. However, fabrication of multifunctional surfaces on polymers in a high-throughput and robust manner at ambient conditions remains challenging. In this study, we employ the cold spray (CS) particle deposition technique to produce multifunctional hybrid surfaces on a flexible polymeric substrate (PET) toward flexible electronics. In this regard, soft metal particles (Sn), are deposited on the polymer surface as an “interlayer” followed by the over-coating of hard metal (Cu) film to create hybrid (Sn + Cu) surfaces. Studies on microstructure, adhesion strength, and water contact angle are conducted to characterize the resulting surface structure. By leveraging the optimum CS settings, multifunctional surfaces with promising electrical conductivity (5.96 × 105 S.m−1), flexibility, adhesive strength, and hydrophobicity (contact angle ≈ 122°) were achieved. Moreover, the antibacterial performance of the surface is confirmed by the in vitro antibacterial tests in a manner that > 99% of the bacteria were inhibited. This work provides a promising strategy for high-throughput manufacturing of multifunctional surfaces (flexible + conductive + antibacterial surfaces) toward multifunctional flexible electronics.
Keywords: Antibacterial coatings; Antibacterial surfaces; Cold spray; Conductive surfaces; Flexible surfaces; High-throughput; Metallisation; Multifunctional surface; Polymer metallization; Polymer surfaces; Antibacterial coating; Cold spray; Flexible electronics; Multifunctional surface; Polymer metallization